Asymptotic Stabilization of Delayed Systems with Input and Output Saturations - Adel Mahjoub; Nabil Derbel (International Journal of Applied Power Engineering (IJAPE), 2017)
We consider in this paper the problem of controlling an arbitrary linear delayed system with saturating input and output. We study the stability of such a system in closed-loop with a given saturating regulator. Using inputoutput stability tools, we formulated sufficient conditions ensuring global asymptotic stability.